VIDEOCARE: Decentralised psychiatric emergency care through videoconferencing - Trondsen Marianne V; Bolle Stein Roald; Stensland Geir Øyvind; Tjora Aksel (BMC, 2012)
Abstract Background Today the availability of specialists is limited for psychiatric patients in rural areas, especially during psychiatric emergencies. To overcome this challenge, the University Hospital of North Norway has implemented a new decentralised on-call system in psychiatric emergencies, by which psychiatrists are accessible by videoconference 24/7. In September 2011, the new on-call system was established in clinical practice for patients and health staff at three regional psychiatric centres in Northern Norway. Although a wide variety of therapies have been successfully delivered by videoconference, there is limited research on the use of videoconferenced consultations with patients in psychiatric emergencies. The aim of this study is to explore the use of videoconference in psychiatric emergencies based on the implementation of this first Norwegian tele-psychiatric service in emergency care. Methods/design The research project is an exploratory case study of a new videoconference service in operation. By applying in-depth interviews with patients, specialists and local health-care staff, we will identify factors that facilitate and hinder use of videoconferencing in psychiatric emergencies, and explore how videoconferenced consultations matter for patients, professional practice and cooperation between levels in psychiatric care. By using an on-going project as the site of research, the case is especially well-suited for generating reliable and valid empirical data. Discussion Results from the study will be of importance for understanding of how videoconferencing may support proper treatment and high-quality health care services in rural areas for patients in psychiatric emergencies.